Leaning against the wind: Debt financing in the face of adversity - Michael J. Brennan; Holger Kraft (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We offer evidence of a new stylized feature of corporate financing decisions: the tendency of managers to rely more on debt financing when earnings prospects are poor. We term this 'leaning against the wind' and consider three possible explanations: market timing, precautionary financing, and 'making the numbers'. We find no evidence in favor of the first two hypotheses, and provisionally accept the 'making the numbers' hypothesis that managers who are under pressure because of unrealistically optimistic earnings expectations by analysts and deteriorating real opportunities, will rely more heavily on debt financing to boost earnings per share and return on equity.
Keywords: G12; G14; G32; 330; Capital structure; financing policy; managerial incentives